Smart nanomaterials for semiconductor applications: Recent advances in energy storage and biosensing technologies - G.K. Prashanth; Srilatha Rao; H.S. Lalithamba; N.P. Bhagya; M. Mahadeva Swamy; S.R. Yashodha; H.S. Yogananda (Next Materials, 2025)
The evolution of nanomaterials has revolutionized the design of functional devices, particularly in semiconductor-based applications. This review critically explores recent advancements in smart nanomaterials for two transformative domains: energy storage and biosensing. Unlike earlier descriptive reviews, it integrates performance comparisons, mechanistic insights, and synthesis–structure–function relationships across diverse nanostructures such as metal oxides, quantum dots (QDs), carbon hybrids, and 2D materials. Key device configurations—including supercapacitors and field-effect transistor (FET)-based biosensors—are examined to highlight how morphological and compositional tuning of nanomaterials affects electrochemical and biorecognition performance. Comparative analysis is supported by data from recent high-impact studies, while unresolved challenges such as scalability, reproducibility, toxicity, and real-world integration are addressed. The novelty of this review lies in its dual-focus framework, juxtaposing materials and mechanisms from both energy and biomedical domains, thus providing unified insights for next-generation multifunctional semiconductor systems. This approach addresses a critical gap in the literature, where most reviews focus exclusively on either energy or biosensing platforms, without considering their overlapping synergies. The final section presents a forward-looking perspective on standardization, biocompatibility, and AI-assisted device integration, emphasizing the roadmap from laboratory research to real-world deployment.